2009
DOI: 10.1021/ol900327x
|View full text |Cite
|
Sign up to set email alerts
|

Rh(I)-Catalyzed CO Gas-Free Carbonylative Cyclization Reactions of Alkynes with 2-Bromophenylboronic Acids Using Formaldehyde

Abstract: The rhodium(I)-catalyzed reaction of alkynes with 2-bromophenylboronic acids in the presence of paraformaldehyde resulted in a CO gas-free carbonylative cyclization, yielding indenone derivatives. [RhCl(BINAP)](2) and [RhCl(cod)](2) were responsible for the decarbonylation of formaldehyde and the subsequent carbonylation of alkynes with 2-haloboronic acids, respectively, leading to efficient whole carbonylation. Sterically bulky and electron-withdrawing groups on unsymmetrically substituted alkynes favored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 36 publications
(20 reference statements)
3
66
0
Order By: Relevance
“…[15] Recent examples include the rhodium-catalyzed reaction of alkynes, o-bromophenylboronic acids, and paraformaldehyde. [16] The Sonogashira reaction [17] has been evidenced to be an efficient approach to conjugated oligomers, [18] dendrimers, [19] and polymers [20] for optoelectronic studies in the fields of organic light-emitting diodes (OLED), [21] organic solar cells, [22] and two-photon absorption. [23] Recently, creased when the reaction was terminated after 7 h (Table 1, entry 4).…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recent examples include the rhodium-catalyzed reaction of alkynes, o-bromophenylboronic acids, and paraformaldehyde. [16] The Sonogashira reaction [17] has been evidenced to be an efficient approach to conjugated oligomers, [18] dendrimers, [19] and polymers [20] for optoelectronic studies in the fields of organic light-emitting diodes (OLED), [21] organic solar cells, [22] and two-photon absorption. [23] Recently, creased when the reaction was terminated after 7 h (Table 1, entry 4).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently Beller et al reported the first industrially applied and efficient palladium-catalyzed reductive carbonylation at 5 bar of synthesis gas (CO/H 2 1:1). [6] Though some successful reports on hydroxy-, [7,8] alkoxy-, [9,10] and aminocarbonylation [11] have been published, there is still only one report on the reductive carbonylation of aryl halides using an external CO source. Various compounds such as formic acid derivatives and metal carbonyl compounds have already been developed as alternatives to toxic CO gas.…”
Section: Tsuyoshi Ueda Hideyuki Konishi and Kei Manabe*mentioning
confidence: 99%
“…[2] Carbonylation reactions have been the focus of extensive research in organic syntheses and industrial processes employing CO as the C1 source. [4] The typical known CO surrogate compounds include methanol, [5] 1,3-dioxolane, [6] formaldehyde, [7] paraformaldehyde, [8] silacarboxylic acids, [9] formic acid and its derivatives, [10] acyl chloride derivatives, [11] carbon dioxide, [12] metal carbonyls, [13] and N-formylsaccharin (NFS). Hence, carbonylation methodology conducted without the use of CO would be a reliable and accessible choice for the further advancement of sustainable chemistry.…”
mentioning
confidence: 99%
“…Palladium-catalyzed reductive carbonylation of aryl halides with N-formylsaccharin and palladium-catalyzed cyclization reactions of methylenecyclopropanes (MCPs) go through different ring-opening patterns. Next, when the amount of the transfer carbonylation reagent NFS and Et 3 SiH were increased from 1.5 to 2.0 eq, both of the conversion of 1 g and the yield of 3 g were increased, affording 3 g in 53% yield ( [7][8][9][10][11][12][13]. Carrying out the reaction at 80°C gave 3 g in the yield of 45% (Table 1, entry 4).…”
mentioning
confidence: 99%